PEMBELAJARAN TEKNIK DASAR SEPAK SILA PERMAINAN SEPAK TAKRAW MELALUI â€œHOOP TAKRAWâ€ PADA SISWA KELAS V SD NEGERI 3 JUNGSEMI KECAMATAN KANGKUNG KABUPATEN KENDAL (Department of Physical Education, Sport, Health and Recreation, 2014)
The learning process is not maximized football precepts and yet achieve mastery in its implementation . Inaddition, students in the material value of sepak takraw especially football precepts still much below themaximum limit of completeness criteria ( KKM ) is 70 . The purpose of this research is to improve learningoutcomes through the basic techniques of soccer games sila